Student as a target market for eBekal: a study of online purchasing at Pernec Technologies / Farrah Wahida Zainal - Zainal, Farrah Wahida (Faculty of Business and Management, 2009)
This research is a study on student as a target market for eBekal at Pernec Technologies, Ampang/Ulu Kelang. Variable such demographics, behavioral and have been identify in order to do this research. The main factor of this research is to identify student characteristics of buying online or offline and which characteristic have significant on online purchasing. The survey is conducted at Pernec Technologies which the sample of this study is students. The students are categorized into age of 18 to 26. They are full time student and presently pursuing their practical training in Pernec Technologies. They comprise of IPTA and IPTS students all over Malaysia. Respondent are required to answer the questionnaire which consist of question that potentially have a relationship with online purchasing. Data are analyse using statistical package of Social Science (SPSS). Mean or average value is the most commonly used measures of central tendency, with the most of the responses distribution around the mean. Standard error is calculated because it is to determine the reliability of the sample. The result shows that, there are a few aspects are highlighted in order to make student as a target market for eBekal based on online purchasing orientation.